Estudo do desgaste abrasivo das resinas compostas disponíveis no mercado brasileiro - Bianchi, Eduardo Carlos [UNESP]; Aguiar, Paulo Roberto De [UNESP]; Poggi, Márcio Rodrigo [UNESP]; Salgado, Manoel Henrique [UNESP]; Freitas, César Antunes De [UNESP]; Bianchi, Ana Rita Rodrigues (ABM, ABC, ABPol, 2003)
This work presents a proposal to assess the abrasive wear of composite resins available in the national market, which are materials largely used in dental clinics for functional and aesthetic tooth restorations. This was achieved by utilizing an experimental set-up on which a dynamic disc covered with proper porcelain (representing hardness close to the human teeth) wears a static disc covered with the resin tested under a constant and pre-determined load. Thus, by means of this set-up and keeping a behavioral status needed to the calculus for all tests, the aggressiveness (referred as to letter k) for all tests was analyzed. Due to the fact that resin characteristic revels how weary the material has become to the abrasion process with other harder material, the strength to wear for such resins was observed. Therefore, a real classification for these materials with their strength to the abrasion wear was made, which is a very important factor in the influence on their lifetime in dental restorations. The classification in descending order for those resins is presented as following: HELIOMOLAR RO, DURAFILL, FILTEK A110, HELIO FILL, POINT 4, FLOW IT; NATURAL FLOW, SUPRAFILL, FILTEK P60, FILTEK Z250, TETRIC FLOW, REVOLUTION, PRODIGY, TETRIC CERAM, HERCULITE, FILLMAGIC, TPH, CHARISMA, Z100.
Keywords: composite resin; abrasive wear; evaluation methods; aggressiveness